How Does Consecutive Interpreting Training Influence Working Memory: A Longitudinal Study of Potential Links Between the Two - Dong, Yanping; Liu, Yuhua; Cai, Rendong (Frontiers in Psychology, 2018)
With an intention to contribute to the issue of how language experience may influence working memory (WM), we focused on consecutive interpreting (CI), analyzed its potential links with WM functions and tested these links in a longitudinal experiment, trying to answer the specific question of how CI training may influence WM. Two comparable groups of Chinese learners of English received either CI or general second language (L2) training for one semester, and were tested before and after the training with the tasks of n-back (nonverbal updating), L2 listening span and letter running span (verbal spans). CI performance was tested in the posttest. The results showed that (1) updating efficiency in both the pretest and posttest predicted CI performance, and CI training enhanced updating efficiency while general L2 training did not; (2) the relationship between verbal spans and CI performance was weaker (i.e., only pretest L2 listening span correlated with CI performance and predicted CI performance with marginal significance), and CI training did not make a unique contribution to these spans (i.e., no group differences). The results indicated an ‘interpreter advantage’ in updating, which was probably due to that updating was more central in the CI task than WM spans. Theoretically, we believe that updating and CI are closely related because they share the same underlying mechanism, or more specifically updating and the recalling process in the CI task share the same attentional control process, a unique link between updating and the CI task. Methodological implications are discussed.